2016
DOI: 10.1007/s00170-016-9704-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-based methods for cost estimation of metal casts

Abstract: The aim of the research presented in this paper was to verify the hypothesis that the problem of estimating the variable costs of metal casts can be solved by using knowledge-based systems. The estimation of variable costs determines the adequate pricing of products, which is a crucial marketing problem in enterprises. The problem of estimating the direct costs is especially important in companies whose participation in the market is defined as versatile manufacturing. This problem was the target of many studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The concept of Takagi and Sugeno may improve an expressiveness/computational efficiency relation both for tasks and classification tasks. Here we can also refer to the results of our research (Maciol 2017), which for a specific case showed an increase of the inference effectiveness expressed as the mean absolute percentage error by about 19% comparing to the results of the Mamdani's method (by 29% in a relation to the classical method) and by 20% comparing to the Mamdani's method (26% in a relation to the classical method) if expressed with the maximal relative deviation. Such a significant increase in the expressiveness is a result of a fact that relations between antecedents and conclusions are not described explicitly but with an arbitrary function.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The concept of Takagi and Sugeno may improve an expressiveness/computational efficiency relation both for tasks and classification tasks. Here we can also refer to the results of our research (Maciol 2017), which for a specific case showed an increase of the inference effectiveness expressed as the mean absolute percentage error by about 19% comparing to the results of the Mamdani's method (by 29% in a relation to the classical method) and by 20% comparing to the Mamdani's method (26% in a relation to the classical method) if expressed with the maximal relative deviation. Such a significant increase in the expressiveness is a result of a fact that relations between antecedents and conclusions are not described explicitly but with an arbitrary function.…”
Section: Introductionmentioning
confidence: 69%
“…Considering the inability of using of sufficiently large training sets in our earlier studies (Maciol 2017), we used the set of equations described with the defined above support points. The solution of the set of equations gave coefficients in the line function sought.…”
Section: The Establishing Of the Parameters In The Consequencesmentioning
confidence: 99%
“…The method works well in mass production foundries making castings of similar characteristics, but it is not suitable for job shop or batch type foundries that have a wide range of products. To alleviate these problems, more elaborate cost models have been proposed by identifying and calculating the detailed cost elements (Sajid et al, 2018;Maciol, 2017). However, very few works have been reported on cost estimation of investment casting.…”
Section: Research Backgroundmentioning
confidence: 99%